The A SURVEY ON SECURE AND EFFICIENT FEATURE BASED PRODUCT INFORMATION RETRIEVAL FROM CLOUD (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
When it comes to managing a big number of IT resources in an effective and adaptable way, cloud computing is an exciting new IT method to watch. Companies are increasingly moving their data management systems to the cloud and storing their product information on cloud servers. As an additional problem, how to keep commercially private data secure while yet allowing for the capacity to search it is a major one. An identifier-based and feature-based product search strategy is suggested in this work to ensure privacy. This is done by creating two new index trees that can be searched without having access to the plaintext data. Analysis and simulation findings show that our system is both secure and efficient